Genetic resources and breeding approaches for improvement of amaranth (Amaranthus spp.) and quinoa (Chenopodium quinoa) - Anuradha; Kumari, Manisha; Zinta, Gaurav; Chauhan, Ramesh; Kumar, Ashok; Singh, Sanatsujat; Singh, Satbeer (Frontiers in Nutrition, 2023)
Nowadays, the human population is more concerned about their diet and very specific in choosing their food sources to ensure a healthy lifestyle and avoid diseases. So people are shifting to more smart nutritious food choices other than regular cereals and staple foods they have been eating for a long time. Pseudocereals, especially amaranth and quinoa, are important alternatives to traditional cereals due to comparatively higher nutrition, essential behavior, available genetic resources, and breeding approaches for these crops to shed light on future breeding strategies to develop superior genotypes.